Sosialisasi Politik Siber untuk Memperkuat Ketahanan Nasional dalam Menghadapi Tantangan Global - M. Prakoso Aji; Subakdi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: This community service activity (PKM) was held to provide socialization of the situation experienced by the community regarding cyber politics to strengthen national resilience in facing global challenges. This PKM activity aims to make residents understand the increasing prevalence of political activities in cyberspace today. With the improvement of the pandemic situation, this socialization activity is carried out in the form of face-to-face or offline. Method: PKM partner is RT. 008, RW. 06 TNI AL Complex, Pondok Labu, Cilandak, South Jakarta. The number of participants was about 20 people. This socialization provides socialization in the form of cyber politics that has a role in strengthening national resilience in facing increasingly widespread global challenges. The material explained is about understanding cyber politics and what policies have been carried out by the government to increase citizens' awareness regarding the importance of having attention to politics to how the public can further raise awareness of the political field, which is currently strongly influenced by technological developments to strengthen national resilience. Results: Increase the erstanding the surrounding community about cyber politics and its relation to national resilience in facing global challenges. Conclusion: In general, it can be concluded that this cyber political socialization activity provides understanding for citizens' need to understand the political dynamics in cyberspace.